(Co)polymerization of (−)-menthide and β-butyrolactone with yttrium-bis(phenolates): tuning material properties of sustainable polyesters. Issue 27 (17th June 2020) - Adams, Friederike; Pehl, Thomas M.; Kränzlein, Moritz; Kernbichl, Sebastian A.; Kang, Jia-Jhen; Papadakis, Christine M.; Rieger, Bernhard
Abstract : Sustainable thermoplastic elastomers derived from block copolymers of syndiotactic poly(3-hydroxybutyrate) and poly((−)-menthide) were synthesized via yttrium-mediated ring-opening polymerization. Abstract : Pyridine-based heteroaromatic yttrium-bis(phenolate) complexes were investigated in ring-opening polymerization of racemic β-butyrolactone (rac-BBL) and (−)-menthide. In addition, AB and BAB copolymers from poly((−)-menthide) (PM, block A) and poly(3-hydroxybutyrate) (PHB, block B) were synthesized via sequential addition. BAB copolymers were accessible through introduction of a bifunctional pyrazine initiator enabling chain growth in two directions. Block copolymers were analyzed using thermal analysis, X-ray diffraction, small-angle X-ray scattering, NMR analysis and stress–strain experiments. These measurements confirmed a microphase separation within the semicrystalline BAB materials. Regarding the mechanical behavior, two hot-moldable PHB-based (co)polymers were investigated. The syndiotactic PHB is less brittle than natural PHB, resulting in a lower Young's modulus. Incorporating PM in the structure, the elastic modulus is further lowered with increasing elongation at break.